Special recipe from pollens for the caste determination of honeybees - Bo Sun (ExRNA, 2019)
Abstract Honeybee caste differentiation is regulated by multiple factors. Here we comment an article published on August 31, 2017, Plos Genetics, which show that miRNAs from pollen may affect honeybee caste formation. Through directly silencing amTOR activity, pollen miR162a can affect ovary development and determine the fate of larvae to differentiate to worker bees. Reciprocally, miRNAs could also regulate flower development to attract more insects in certain plant species. In addition, their finding provides a novel angle to investigate the co-evolution between plants and insects and gives a clue to explain a recent trend of mysterious death of wild honeybees. Therefore, further exploring miRNAs’ function in plant-insect co-evolution is potentially valuable for enhancing agricultural yields.